2001
DOI: 10.1007/s101510070006
|View full text |Cite
|
Sign up to set email alerts
|

Computerized anal vector manometric analysis in patients treated by tailored lateral spincterotomy for anal fissure

Abstract: FACL, 3.30 ± 0.25 cm; HPS, 1.05 ± 0.36 cm; D1/D2 =1.18 ± 0.46). The percent MRAP reduction was nearly constant after TLS, regardless of the type of patients (36.85 ± 15.04% in hypertensives, 30.48 ± 16.62% in normotensives). TLS resulted in hypotonia, which was more evident in females (MRAP = 57.00 ± 7.75 cm H 2 O) and normotensive patients (MRAP = 48.60 ± 9.08 cm H 2 O). Two patients (6.66%) had persistent fissure after TLS. Soiling and imperfect control of flatus were reported by two patients (6.66%). Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…This group of patients had a high pressure profile along the entire anal canal, which reached a maximum 2 cm from the anal verge (p<0.05). A similar experience was recently reported [16]. This observation suggests that the posterior midline is more disposed to injury than the other anal areas, and is in accordance with the ischemic theory.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This group of patients had a high pressure profile along the entire anal canal, which reached a maximum 2 cm from the anal verge (p<0.05). A similar experience was recently reported [16]. This observation suggests that the posterior midline is more disposed to injury than the other anal areas, and is in accordance with the ischemic theory.…”
Section: Discussionsupporting
confidence: 87%
“…Tailored sphincterotomy, devised to reduce the amount of sphincter division, reduces the anal resting pressure by 30%-35% and produces significantly lower incontinence rates [16]. It is difficult to explain why there is anal hypertonia and, at present, we are not able to discriminate if high resting anal pressures are the expression of a local spasm in response to pain caused by the fissure or a primary etiologic factor.…”
Section: Discussionmentioning
confidence: 59%
“…We enjoyed the article by Garcea et al . [1] and note that there are very few prospective studies assessing the functional outcome following lateral internal anal sphincterotomy for chronic anal fissure, particularly when it is minimized in its extent [2]. Pescatori et al .…”
mentioning
confidence: 99%
“…We enjoyed the article by Garcea et al [1] and note that there are very few prospective studies assessing the functional outcome following lateral internal anal sphincterotomy for chronic anal fissure, particularly when it is minimized in its extent [2]. Pescatori et al [3] have shown that there appears to be less faecal soiling after this procedure when tailored sphincterotomy is reserved for topically resistant chronic anal fissure if the pre-operative manometry of the patient is normal or when standard length sphincterotomy from the dentate line is performed for patients with pre-operative resting anal sphincter hypertonia.…”
mentioning
confidence: 99%